Market break or simply fake? Empirics on the causal effects of rent controls in Germany - Konstantin A. Cholodilin; Andreas Mense; Claus Michelsen (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Rising rents in German cities have led to an intense debate about the need for tighter rent controls in housing markets. In April 2015, the so-called rental brake was introduced, which imposes upper bounds for rents in new contracts, in order to immediately slow down the increase of rents in tight housing markets. Since then, 11 federal states made use of this instrument. We take advantage of this intra-country variation and test whether the regulation had a causal effect on rents and house prices in the short run. We apply a standard difference-in-differences setup that allows us to study the effects of the rental brake on the underlying price trend in neighboring treated and non-treated postal-code districts. We ground our analysis on a large sample of online advertised rental dwellings and find that, contrary to the expectations of the policy makers, the rental brake has, at best, no impact in the short run. At worst, it even accelerates rent increases both in municipalities subject to the rental brake and in neighboring areas. We further conclude, based on our estimates on the development of at prices, that investors expect on little impact on future rental income.
Keywords: K23; N9; R30; 330; housing policy; rental housing; Germany; rent controls; rental brake